Rente im Dritten Reich Die Reichsversicherungsanstalt für Angestellte 1933 bis 1945 - Erker, Paul 1959- (De Gruyter, 2019)
Scant research attention has addressed the role, significance, and function of the RfA in the maintenance and reformulation of the retirement insurance system in the Nazi society transformed by the ideology of the Volksgemeinschaft. For the first time, based on primary sources, this book presents a problem-oriented administrative history that investigates the place of the RfA in the National Socialist institutional structure